A biosynthetic regulated secretory pathway in constitutive secretory cells (The Rockefeller University Press, 1996)
It has frequently been proposed that while the constitutive secretory pathway is present in all cells, the regulated secretory pathway is found only in specialized cells such as neuronal, endocrine, or exocrine types. In this study we provide evidence that suggests that this distinction is not as restrictive as proposed. We have identified a population of post-Golgi storage vesicles in several constitutive secretory cells using [35S]SO4-labeled glycosaminoglycan (GAG) chains as a marker. A fraction of this pool of vesicles can undergo exocytosis in response to stimuli such as cytoplasmic Ca2+ and phorbol esters. The effect of Ca2+ was demonstrated both in intact cells in the presence of the ionophore A23187 and in streptolysin-O-permeabilized semi-intact cells. N-ethylmaleiimide, under conditions known to block regulated and constitutive secretion, inhibited the stimulated secretion from these cells, suggesting that the observed release of labeled GAG chains was not due to a leakage artefact. Subcellular fractionation revealed that the stored GAG chains were in low-density membrane granules (d approximately 1.12 g/ml), whose size was greater than that of synaptic- like vesicles found in PC12 cells. In addition, in CHO cells that express epitope-tagged rab 3D, the labeled GAG chains were found to cofractionate with the exogenous rab protein. When expressed in the regulated cell line AtT-20, this tagged rab protein was found to colocalize with ACTH-containing dense-core granules by indirect immunofluorescence. Taken together, these results provide evidence for the presence of a cryptic regulated secretory pathway in "constitutive" cells and suggest that the regulated secretory pathway is more widespread amongst different cell types than previously believed.